2017
DOI: 10.3141/2628-11
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption and Cost Savings of Truck Electrification for Heavy-Duty Vehicle Applications

Abstract: An evaluation was made of the application of battery electric vehicles (BEVs) and GenSet plug-in hybrid electric vehicles (PHEVs) to Class-7 local delivery trucks and GenSet PHEV for Class-8 utility bucket trucks over widely real-world driving data performed by conventional heavy-duty trucks. GenSet refers to a PHEV range extension mode in which the PHEV engine is used only to generate electricity and charge the battery if the PHEV battery is out of electrical energy. A simulation tool based on vehicle tractiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…HDVs comprising heavy-duty trucks and buses account for only 10% of the global vehicle stock but are responsible for 46% of the greenhouse gas emissions from road transport 2 . Electrifying the HDV segment can lead to substantial energy, climate and air quality benefits 3 . Intensive efforts are being made by global entrepreneurs to achieve breakthroughs in HDV electrification technologies and production 2 .…”
Section: Introductionmentioning
confidence: 99%
“…HDVs comprising heavy-duty trucks and buses account for only 10% of the global vehicle stock but are responsible for 46% of the greenhouse gas emissions from road transport 2 . Electrifying the HDV segment can lead to substantial energy, climate and air quality benefits 3 . Intensive efforts are being made by global entrepreneurs to achieve breakthroughs in HDV electrification technologies and production 2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, a limited number of studies has devised methods to estimate energy consumption for electric trucks ( 1618 ). Gao et al developed a simulation tool for estimating electric truck tractive energy considering second-by-second vehicle speed and component efficiency ( 19 ). They found that both the battery electric and plug-in hybrid electric trucks are more energy efficient than conventional diesel trucks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, looking at the pollution, global warming, and the alertness regarding nonconventional energy conservation, power engineers are paying more attention to the design of zero‐polluting ECs. Therefore, to improve the stability and performance of the ECs, the lesser weight EC modeling is gaining interest on an augmented pace 1 . Lots of EC modeling methods are proposed to facilitate a wider driving choice and smoother operation 2 .…”
Section: Introductionmentioning
confidence: 99%